Desain Media Pembelajaran Bahasa Arab Memanfaatkan Articulate Storyline di MAN 1 Boyolali - Rachmawati, Annisa Eka; Masruro, Lailatul (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
The research’s problem is the lack of using Arabic language learning media at MAN 1 Boyolali. Therefore, the objectives of this study are 1) to develop interactive Arabic language learning media based on Articulate Storyline, 2) to determine the feasibility of media, and 3) to determine the response of class X MIPA 4 students. This study used a R&D method with the Borg & Gall model which consists of 6 steps. Material and media experts validate the product. Then the researcher conducted a product trial on 32 class X MIPA 4 students. The results are: 1) Learning media developed by the Articulate Storyline application which can be accessed online via smartphone, laptop, and computer. 2) Learning media in the feasible category based on the assessment of material and media experts with an ideal percentage of 83.529% and 95.384%. 3) The response of students is very good. Students are engrossed and enjoy learning with the media.